Energy and exergy analyses of flat plate solar collectors with nanofluids containing different size and shape of nanoparticles. (17th March 2021) - Uddin, Mohammed Ayaz; Sahin, Ahmet Z.; Yilbas, Bekir Sami; Al-Sharafi, Abdullah
The effect of nanoparticle size, shape, and volume concentration upon the flat plate solar collector (FPSC) performance is investigated. The enhancement in efficiency due to volume concentration SiO2 /H2 O nanofluid was significant whereas the enhancement due to size and shape was marginal. In addition, the paper discusses the effect of the concentration, size and shape of nanoparticles upon the pressure drop, pumping power, exergy destruction and entropy generation. The exergy efficiency is found to increase upon increasing the nanoparticle size and volume concentration. However, the effect due to shape variation on the exergy efficiency is minimal.